Endovascular Treatment of Extracranial Arteriovenous Malformations: A Retrospective Monocentric Case-Series Study - Giuseppe Sarti; Giovanni Barbato; Francesco Tiralongo; Gianpaolo Santini; Francesco Arienzo; Davide Nilo; Fabio Tortora; Alfonso Reginelli; Rosita Comune; Maria Borrelli; Stefania Tamburrini; Antonio Basile; et al. (Tomography, 2025)
Background: Extracranial arteriovenous malformations (AVMs) are rare congenital vascular anomalies that often require endovascular treatment due to symptoms such as pain, bleeding, or functional impairment. Endovascular strategies include arterial, venous, or combined embolization approaches; however, recurrence remains a major challenge. We retrospectively evaluate the technical success, safety, and clinical outcomes of arterial-only versus combined arterial and venous embolization for the treatment of extracranial AVMs. Materials and Methods: This single-center retrospective study included 14 patients (mean age 31.8 ± 21.7 years; 64% female) with symptomatic extracranial AVMs (Schobinger stage II) treated between 2017 and 2023. AVMs were classified angiographically (Yakes classification) and treated with embolization via arterial or combined access routes. The primary endpoint was technical success (defined as angiographic nidus occlusion), while secondary endpoints included clinical recurrence and procedure-related complications. Follow-up included clinical and Doppler ultrasound assessments. Results: Nine patients (64%) underwent arterial embolization alone; five (36%) received combined arterial and venous embolization, including Lauromacrogol injection via direct puncture. Technical success was achieved in all cases (100%). Clinical recurrence occurred in two patients (14%), both from the arterial-only group. One major complication (tongue ischemia) occurred in a single patient (7%). No complications or recurrences were observed in the combined treatment group. Statistical analysis showed no significant difference in recurrence or complication rates between groups.